2023
DOI: 10.1136/bmjsem-2023-001636
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk and systemic inflammation in male professional rugby: a cross-sectional study

Clíodhna McHugh,
Karen Hind,
Aine Kelly
et al.

Abstract: ObjectiveTo investigate cardiovascular risk factors’ prevalence and association with systemic inflammation in professional male rugby players (RP).MethodsA cross-sectional investigation of 46 professional male RP (26.1±4.1 years) cardiovascular risk factors were compared by position. Inflammatory markers were compared with healthy controls (n=13) and patients with rheumatoid arthritis (RA) (n=10).ResultsTwenty-six per cent of RP had no risk factors, 49% had 1–2 cardiovascular risk factors and 25% had 3–4 risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Although some research has found favorable lipid profiles in rugby players compared to non-athlete controls [21], other studies have reported equivocal findings [22] or a high prevalence of atherogenic lipid profiles and other risk factors for CVD [23][24][25]. The majority of male professional rugby players have one or more CVD risk factors [26], and a significantly higher incidence of hypertension and diabetes has been reported in rugby players compared to the general population [25]. Recommendations have therefore been made that rugby players engage in preventative strategies to mitigate their elevated CVD risk [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although some research has found favorable lipid profiles in rugby players compared to non-athlete controls [21], other studies have reported equivocal findings [22] or a high prevalence of atherogenic lipid profiles and other risk factors for CVD [23][24][25]. The majority of male professional rugby players have one or more CVD risk factors [26], and a significantly higher incidence of hypertension and diabetes has been reported in rugby players compared to the general population [25]. Recommendations have therefore been made that rugby players engage in preventative strategies to mitigate their elevated CVD risk [25].…”
Section: Introductionmentioning
confidence: 99%